2022
DOI: 10.1039/d2cp00646d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation of glycerol-derived triether podands for lithium ion solvation

Abstract: Solvated ionic liquids (ILs) are promising candidates for electrolytes in next-generation lithium-ion batteries, due to their stability, high coulombic efficiency, and low volatility. In this work, we investigate the solvation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Modeling fluid phase equilibria in aqueous–organic–electrolyte mixtures across a wide range of salinities are challenging given the range of complex phenomena arising from the interactions between polar solvent molecules and ions. Atomistic simulations of biphasic mixtures comprising water and salts mixed with amine-, imidazole-, , carboxylic-acid, or ionic-liquid-based solvents have shown that small, highly charged ions have a strong impact on water–solvent interactions and structure in both phases. In this study, the semiempirical electrolyte nonrandom two-liquid (eNRTL) model is used to capture the excess Gibbs free energy false( normale normalx false) of highly nonideal mixtures of water, DME, and sodium chloride (NaCl), with adjustable parameters estimated using experimental data.…”
Section: Thermodynamic Modelsmentioning
confidence: 99%
“…Modeling fluid phase equilibria in aqueous–organic–electrolyte mixtures across a wide range of salinities are challenging given the range of complex phenomena arising from the interactions between polar solvent molecules and ions. Atomistic simulations of biphasic mixtures comprising water and salts mixed with amine-, imidazole-, , carboxylic-acid, or ionic-liquid-based solvents have shown that small, highly charged ions have a strong impact on water–solvent interactions and structure in both phases. In this study, the semiempirical electrolyte nonrandom two-liquid (eNRTL) model is used to capture the excess Gibbs free energy false( normale normalx false) of highly nonideal mixtures of water, DME, and sodium chloride (NaCl), with adjustable parameters estimated using experimental data.…”
Section: Thermodynamic Modelsmentioning
confidence: 99%
“…32 Since TMP was rst synthesized, several uses for this solvent have been explored, including as an oxygenated bio-sourced additive for fuels, solvent for the reduction of organic functions, and for CO 2 capture. Barbosa et al 33 further investigated the thermophysical properties of TMP and simulated the ability of TMP to dissolve and coordinate metal cations such as Li + , an important feature for electrolyte solvents as the solvation determines the chemical and electrochemical environment of ions and the transport properties, which ultimately affect battery performance. They found the presence of Li + induces a crown-like coordination with the oxygen in the TMP molecule, which is similar in DGME.…”
Section: Introductionmentioning
confidence: 99%
“…12 In this last publication, Bara et al highlighted the thermophysical properties of TMP and suggested the potential of this molecule for the solvation of metal cations such as Li + , as confirmed later by preliminary Molecular Dynamics (MD) simulations. 18 However, to the best of our knowledge TMP has not been investigated as electrolyte in lithium batteries.…”
Section: Introductionmentioning
confidence: 99%